Livestock Science - Sekkin, Selim (IntechOpen, 2017)
There has been a great increase in the consumption of animal products. The intention of agricultural activities is to provide safety and adequate food by respecting the environment. Although many questions are being raised concerning the sustainability of the world's food-animal agricultural resources. This book presents some in-depth reviews of selected topics in livestock science written by experts in their respective areas. The book is divided into eight chapters, consisting of topics in food-animal production systems, management of several animal products, health-threaten example by ticks in animals, and contaminants that may be found in animal foods. We hope that a wide variety of scientists, researchers, and others may benefit from this book.